A Model of Superinfection of Virus-Infected Zebrafish Larvae: Increased Susceptibility to Bacteria Associated With Neutrophil Death - Boucontet, Laurent; Passoni, Gabriella; Thiry, Valéry; Maggi, Ludovico; Herbomel, Philippe; Levraud, Jean-Pierre; Colucci-Guyon, Emma (Frontiers in Immunology, 2018)
Enhanced susceptibility to bacterial infection in the days following an acute virus infection such as flu is a major clinical problem. Mouse models have provided major advances in understanding viral-bacterial superinfections, yet interactions of the anti-viral and anti-bacterial responses remain elusive. Here we have exploited the transparency of zebrafish to study how viral infections can pave the way for bacterial co-infections. We have set up a zebrafish model of sequential viral and bacterial infection, using sublethal doses of Sindbis virus and Shigella flexneri bacteria. This virus induces a strong type I IFN response while the bacterium induces a strong IL1β and TNFα-mediated inflammatory response. We found that virus-infected zebrafish larvae showed an increased susceptibility to bacterial infection. This resulted in the death with concomitant higher bacterial burden of the co-infected fish compared to the ones infected with bacteria only. By contrast, infecting with bacteria first and virus second did not lead to increased mortality or microbial burden. By high-resolution live imaging we showed that neutrophil survival was impaired in Sindbis-then-Shigella co-infected fish. The two types of cytokine responses were strongly induced in co-infected fish. In addition to type I IFN, expression of the anti-inflammatory cytokine IL10 was induced by viral infection before bacterial superinfection. Collectively, these observations suggest the zebrafish larva as a useful animal model to address mechanisms underlying increased bacterial susceptibility upon viral infection.